2019
DOI: 10.3390/v11121114
|View full text |Cite
|
Sign up to set email alerts
|

Equine Mx1 Restricts Influenza A Virus Replication by Targeting at Distinct Site of its Nucleoprotein

Abstract: Interferon-mediated host factors myxovirus (Mx) proteins are key features in regulating influenza A virus (IAV) infections. Viral polymerases are essential for viral replication. The Mx1 protein has been known to interact with viral nucleoprotein (NP) and PB2, resulting in the influence of polymerase activity and providing interspecies restriction. The equine influenza virus has evolved as an independent lineage to influenza viruses from other species. We estimated the differences in antiviral activities betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Next, we aimed to uncover the underlying mechanisms by which ZCCHC3 inhibits H9N2 infection. In recent years, accumulating evidence showed that the host factors, including Mx1 and ISG20 could markedly inhibit influenza virus replication through modulating innate immune response ( Fatima et al., 2019 ; Qu et al., 2016 ). Hence, we investigated whether ZCCHC3 affected innate signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we aimed to uncover the underlying mechanisms by which ZCCHC3 inhibits H9N2 infection. In recent years, accumulating evidence showed that the host factors, including Mx1 and ISG20 could markedly inhibit influenza virus replication through modulating innate immune response ( Fatima et al., 2019 ; Qu et al., 2016 ). Hence, we investigated whether ZCCHC3 affected innate signaling.…”
Section: Resultsmentioning
confidence: 99%
“…The Mx (myxovirus) gene encoding an ~75 kDa protein was the first ISG to be discovered to confer resistance to influenza virus infection [ 8 , 9 , 10 , 11 , 12 ]. Except for chickens [ 13 , 14 , 15 , 16 ], Mx proteins in the majority of influenza virus hosts, e.g., humans [ 17 ], pigs [ 18 , 19 ], and horses [ 20 ], exhibit antiviral activity. Mx proteins are dynamin-like GTPases [ 21 , 22 , 23 ], which oligomerize into ring-like structures [ 24 , 25 , 26 , 27 , 28 ] and target influenza virus vRNPs to exert their antiviral function [ 29 , 30 ].…”
Section: Isgsmentioning
confidence: 99%
“…Mx proteins are dynamin-like GTPases [ 21 , 22 , 23 ], which oligomerize into ring-like structures [ 24 , 25 , 26 , 27 , 28 ] and target influenza virus vRNPs to exert their antiviral function [ 29 , 30 ]. Human Mx protein interacts with viral NP and PB2 to sense and sequester the incoming vRNPs in the cytoplasm and inhibit their nuclear import and subsequent viral RNA transcription and replication [ 20 , 29 , 30 , 31 , 32 , 33 ]. Human Mx protein is a barrier to the zoonotic transmission of avian influenza viruses and recently discovered bat influenza viruses to humans [ 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Isgsmentioning
confidence: 99%
“…Likewise, Mx1 proteins are part of the species barrier against IAVs in other mammalian species. Equine Mx1 blocks avian and human IAVs, whereas equine IAVs have escaped from restriction [ 12 ]. Similarly, porcine Mx1 inhibits avian IAVs, but is only weakly active against swine or human IAVs [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%